A Comparison of DSM-IV-TR and DSM-5 Definitions for Sexual Dysfunctions: Critiques and Challenges - (:unkn) unknown (ELSEVIER SCI LTD, 2014)
Introduction. The diagnostic criteria of sexual dysfunctions (SDs) are paramount for the development of sexual medicine as reliable diagnoses are essential to guide treatment plans. Prior Diagnostic and Statistical Manual of Mental Disorders (DSM) classifications based definitions of SD mostly on expert opinions and included imprecise terms. The validity of diagnoses of SD has only recently been challanged, and efforts are made to make more operational definitions. Aim. This paper aims to compare and contrast the recently released Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition (DSM-5) diagnostic criteria of SD with that of Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition Text Revision (DSM-IV-TR) and explains the rationale for making changes in the new DSM-5. It also aims to address some issues to be considered further for the future. Methods. Online proposed American Psychiatric Association website DSM-5, the new released DSM-5, and DSM-IV-TR diagnostic criteria for SD were throughly inspected, and an extensive literature search was performed for comparative reasons. Main Outcome Measures. Changes in diagnostic criteria of DSM-5 were detected, and DSM-IV-TR and DSM-5 diagnostic criteria for SD were compared and contrasted. Results. Diagostic criteria were more operationalized, and explicit duration and frequency criteria were set up in DSM-5 for purposes of good clinical research. Classifications based on simple linear sexual response were abondoned, and diagnostic classifications were separetely made for males and females. Desire and arousal disorders in women were merged. Conclusions. Drifting apart from linear sexual response cycle may be an advancement in establishing specific diagnostic criteria for different genders. However, it is still a question of debate whether there is enough evidence to lump sexual interest and arousal disorders in females. Making more precise definitions is important to differentiate disorders from other transient conditions. However, there is still room to improve our definitions and find a way to include gay and lesbian individuals. Further discussions and debates are expected to be continued in the future.
Keywords: Sexual Dysfunctions; Critiques; Challenges; DSM-5; DSM-IV-TR; Definitions for Sexual Dysfunctions; MALE ORGASMIC DISORDER; DIAGNOSTIC-CRITERIA; PREMATURE EJACULATION; UNINTENDED CONSEQUENCES; ERECTILE DYSFUNCTION; LIKELY IMPLICATIONS; RAPID EJACULATION; WOMEN; AROUSAL; CLASSIFICATION